Funding self-employment: The role of consumer credit - Christoph Kneiding; Alexander S. Kritikos (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This paper investigates whether self-employed households use consumer loans - in particular instalment loans and overdrafts - to finance business activities. Controlling for financial and non-financial household variables we show that self-employed households particularly use personal overdrafts significantly more often than employee households. When analyzing the correlation between consumer loan takeups and consumption of self-employed in comparison to employee households, we find first evidence that overdrafts are used by self-employed to finance their business as well. This indicates that intermingling constitutes a financing strategy when regular business loans might not be accessible.
Keywords: G32; D12; D14; 330; Small Business Finance; Consumer Credit; Financial Intermingling